Functional Diagnostics for Signaling Positions of Commutation Apparatuses in Electrical Installations - V. A. Anishchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper investigates functional diagnostics for signaling positions of automatic switches, disconnectors and their earthing knives that permit timely to reveal mistaken results of signaling.